Feeding Behaviour of Sheep Fed With Cultivated Fodders Under Intensive System - V Ramesh, Ramya; Muralidharan, J; Sivakumar, K (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Experiment was carried out at Instructional Livestock Farm complex, Veterinary college and Research Institute, Namakkal, Tamil Nadu during 2015-2016 and with the aim to study the feeding behaviour of sheep fed with cultivated hybrid napier and multicut fodder sorghum at different stage of cuttings under intensive system. Intensity of eagerness towards the green fodders and bouts length, duration and frequency were studied. The intensity of eagerness towards the fodder was highest in CO(BN)5 group followed by CO(CN)4 and COFS29 at 60th and 75th days of cuttings. The number of bites per min was highest in CO(BN)5 group whereas the bout time (min) and frequency of bite was highest in CO(CN)4 group and lowest in COFS29 group.
Keywords: Mecheri sheep; Feeding behaviour; Different fodders